Physician organization care management capabilities associated with effective inpatient utilization management: a fuzzy set qualitative comparative analysis - Sheehy, Thomas J (BMC Health Serv Res, 2014)
BACKGROUND: We studied the relationship between physician organization (PO) care management capabilities and inpatient utilization in order to identify PO characteristics or capabilities associated with low inpatient bed-days per thousand. METHODS: We used fuzzy-set qualitative comparative analysis (fsQCA) to conduct an exploratory comparative case series study. Data about PO capabilities were collected using structured interviews with medical directors at fourteen California POs that are delegated to provide inpatient utilization management (UM) for HMO members of a California health plan. Health plan acute hospital claims from 2011 were extracted from a reporting data warehouse and used to calculate inpatient utilization statistics. Supplementary analyses were conducted using Fisher’s Exact Test and Student’s T-test. RESULTS: POs with low inpatient bed-days per thousand minimized length of stay and surgical admissions by actively engaging in concurrent review, discharge planning, and surgical prior authorization, and by contracting directly with hospitalists to provide UM-related services. Disease and case management were associated with lower medical admissions and readmissions, respectively, but not lower bed-days per thousand. CONCLUSIONS: Care management methods focused on managing length of stay and elective surgical admissions are associated with low bed-days per thousand in high-risk California POs delegated for inpatient UM. Reducing medical admissions alone is insufficient to achieve low bed-days per thousand. California POs with high bed-days per thousand are not applying care management best practices. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12913-014-0582-5) contains supplementary material, which is available to authorized users.